My old dog : rescued pets with remarkable second acts - Coffey, Laura T., 1970- (New World Library, 2015)
""No Dog Should Die Alone" was the attention-grabbing - and heart-stirring - headline of journalist Laura T. Coffey's TODAY show website story about photographer Lori Fusaro's work with senior shelter pets. While generally calm, easy, and already house-trained, these animals often represent the highest-risk population at shelters. With gorgeous, joyful photographs and sweet, funny, true tales of "old dogs learning new tricks," Coffey and Fusaro show that adopting a senior can be even more rewarding than choosing a younger dog. You'll meet endearing elders like Marnie, the irresistible shih tzu who has posed for selfies with Tina Fey, James Franco, and Betty White; Remy, a soulful nine-year-old dog adopted by elderly nuns; George Clooney's cocker spaniel, Einstein; and Bretagne, the last known surviving search dog from Ground Zero. They may be slower moving and a tad less exuberant than puppies, but these pooches prove that adopting a senior brings immeasurable joy, earnest devotion, and unconditional love"--